2011
DOI: 10.1007/s11738-011-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

Hairy root culture of Picrorhiza kurroa Royle ex Benth.: a promising approach for the production of picrotin and picrotoxinin

Abstract: Picrorhiza kurroa Royle ex Benth. is an endangered plant producing various compounds of medicinal importance. Hairy roots of P. kurroa were obtained following cocultivation of shoot tip explants with Agrobacterium rhizogenes strains A 4 and PAT 405. Bacterial strain A 4 appeared to be better than the strain PAT 405 in terms of both growth of respective hairy root cultures and secondary metabolite production. The optimal growth of both the hairy root cultures occurred on halfstrength semisolid medium with 3% su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The fresh weight and dry weight after lyophilization were determined determined. The powdered samples (0.5 g DW) were extracted with 100 ml of 70% ethanol in a soxhlet apparatus, and then dried crude extract was dissolved in 10 ml of water:methanol:isopropanol: acetonitrile (60:30:5:5) and quantification by HPLC was done using standards (Purohit et al, 2008;Mishra et al, 2011b). A standard curve was prepared by 10, 20, 30, 40 and 50 mg/L solutions of picrotin and picrotoxin standard (Sigma Chemical Company, St. Louis, USA).…”
Section: Extraction Of Active Ingredientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fresh weight and dry weight after lyophilization were determined determined. The powdered samples (0.5 g DW) were extracted with 100 ml of 70% ethanol in a soxhlet apparatus, and then dried crude extract was dissolved in 10 ml of water:methanol:isopropanol: acetonitrile (60:30:5:5) and quantification by HPLC was done using standards (Purohit et al, 2008;Mishra et al, 2011b). A standard curve was prepared by 10, 20, 30, 40 and 50 mg/L solutions of picrotin and picrotoxin standard (Sigma Chemical Company, St. Louis, USA).…”
Section: Extraction Of Active Ingredientsmentioning
confidence: 99%
“…Detection was done at 220 nm using UV detector L 7400. The calculations of picrotin and picrotoxinin were carried out on peak area basis using standard curves made with reference standard compound (Mishra et al 2011b). …”
Section: Hplc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…8 The biosynthetic potential of the transformed roots is genetically controlled but it has frequently been observed that such transformed roots are sensitive to medium composition with respect to both biomass yield and secondary metabolite productivity. 5,9,10 Several groups have shown that besides selection of superior hairy root clones with higher than average productivity, media optimization could enhance the biomass as well as secondary metabolite yield. 5,10 We previously reported A. rhizogenes mediated transformation of this medicinally imperative plant species for the production of the desired phytochemicals (i.e., Picropside I and Kutkoside).…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 Several groups have shown that besides selection of superior hairy root clones with higher than average productivity, media optimization could enhance the biomass as well as secondary metabolite yield. 5,10 We previously reported A. rhizogenes mediated transformation of this medicinally imperative plant species for the production of the desired phytochemicals (i.e., Picropside I and Kutkoside). 5 In present study we optimized the different parameters to enhance productivity of picroliv from hairy roots of P. kurroa.…”
Section: Introductionmentioning
confidence: 99%